Cooperative non-covalent interactions and synthetic feed as driving forces to structural diversity within organic co-crystals containing isosteric perhalobenzenes. Issue 21 (19th May 2022) - Bosch, Eric; Ferrence, Gregory M.; Powell, Conrad J.; Unruh, Daniel K.; Krueger, Herman R.; Groeneman, Ryan H.
Abstract : Structural diversity is achieved in a series of halogen-bonded co-crystals based upon cooperative non-covalent interactions and the synthetic feed of the components. Abstract : The formation of three co-crystals based upon a pair of isosteric halogen-bond donors, namely 1, 4-diiodoperchlorobenzene and 1, 4-diiodoperfluorobenzene, along with the acceptor trans -1-(4-methylbenzoate)-2-(4-pyridyl)ethylene is reported. Along with the varied stoichiometric ratios of the components, the ability of 1, 4-diiodoperchlorobenzene to engage in cooperative Cl⋯O halogen bonds while 1, 4-diiodoperfluorobenzene forms C–H⋯F interactions leads to the structural diversity of these co-crystals.